IDENTIFICATION OF MISCONCEPTIONS OF HUMAN SENSORY MATTER USING THE CERTAINTY OF RESPONSE INDEX (CRI) METHOD - Helmalia Putri; Anatri Desstya (Jurnal Cakrawala Pendas, 2024)
The material of the five senses in humans is one of the materials that often causes errors for students in solving problems. This study aims to a) identify student misconceptions using the Certainty of Response Index (CRI) method of human sensory material in grade IV elementary school students, b) describe the causes of misconceptions. This study used a qualitative descriptive approach. This research was conducted at SD Negeri Srimulyo 2 Sragen, with the subject of the study being grade IV students as many as 15 children. The data collection techniques used are tests, interviews and documentation. The research instrument used is 15 questions accompanied by CRI that has been tested for validity and reliability. The wetness test in this study used a triangulation method, namely by comparing test results with interview results. The data was analyzed by referring to CRI categorization which was used to measure the level of confidence of learners about the answers they gave, so as to distinguish learners who guessed, understood concepts, did not understand concepts, and misconceptions. The results showed that a) as many as 41.93% or there were 6 students experiencing misconceptions. The highest misconception of this study is on the indicators of the function of the five senses of humans, while the lowest misconception is on indicators of understanding and types of five senses., b) there are several factors that cause misconceptions, namely the difficulty of students in memorizing the material, the lack of interest in learning students, and inappropriate teacher teaching methods. Thus, there is a need for innovation and evaluation for and teachers to improve the use of learning methods and media.